LINGUOPOETIC ANALYSIS OF SOME PROVERBS USED IN “DEVONU LUGOTIT TURK” (Scientific journal of the Fergana State University, 2024)
The article describes the proverbs that are paremic units, and the theoretical opinions on their linguopoetic analysis. One of the common types of folklore is a proverb. Proverb is one of the sub-genres of our oral creativity. Although the proverbs are short in length, the thought and content are comprehensive. Proverb is one of the international genres by its nature. There is no nation in the world that does not have its own proverbs. Because every nation leaves its life experiences to generations in the form of proverbs. It is important to use proverbs in the speech process. In proverbs, the addressee's judgment, opinion, and advice are concisely and clearly expressed.The use of proverbs and sayings in the speech increases the effectiveness of the speech. That's why proverbs are very common and have been used continuously for centuries in live speech, artistic, historical works, journalism, and this process continues even now. A number of proverbs are also mentioned in the work "Devonu lugotit turk", and the metaphorical proverbs are analyzed in this article. Their variants found in the current Uzbek literary language are listed.